Respon Produksi dan Kualitas Buah Salak Gula Pasir (Salacca zalacca var. Gula Pasir) terhadap Dosis Pupuk Hayati Mikoriza - NADA SAHARA; I NYOMAN RAI; I WAYAN WIRAATMAJA (Agrotrop : Journal on Agriculture Science, 2021)
Production and Quality of Salak Gula Pasir (Salacca zalacca var. Gula Pasir) in Response to Application of Dosages of Mycorrhiza Biofertilizer. Mycorrhiza is a fungus that live symbiosis mutualism with the root of the plant. Mycorrhiza has several benefits that improve the soil structure an increase the absorption of nutrients and water for plant. This research aimed to know response of production and quality of salak gula pasir (salacca zalacca var. Gula Pasir) fruit to dose of mycorrhiza biofertilizer application. This study used a randomized block design (RBD) with 4 levels of mycorrhiza biofertilizer dosages, i.e. 0, 50, 100, and 150 spores per 500 g of carrier media. Each treatment was repeated 10 times. The results showed mycorrhiza dose of 50, 100, and 150 spores per 500 g carrier media increase the amount of fruits bunches in each plant, the sweetness level of fruit and root infections/colonization by mycorrhiza.